Next generation sequencing of gonadal transcriptome suggests standard maternal inheritance of mitochondrial DNA in Eurhomalea rufa (Veneridae) - Lubosny, Marek; Przylucka, Aleksandra; Sanko, Tomasz J.; Smietanka, Beata; Rosenfeld Sekulovic, Sebastián Alejandro; Burzynski, Artur (My University, 2017)
Contrary to some of its relatives from Veneridae family, such as Venerupis philippinarium, the clam Eurhomalea rufa lacks doubly uniparental inheritance system of mitochondria. Here we present the argument for strict maternal inheritance of mitochondria in this species, based on next-generation sequencing of gonadal transcriptomes. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: bivalvia; ngs; mitochondria; dui